2008
DOI: 10.1007/s10494-008-9173-z
|View full text |Cite
|
Sign up to set email alerts
|

Two- and Four-Way Coupled Euler–Lagrangian Large-Eddy Simulation of Turbulent Particle-Laden Channel Flow

Abstract: Large-eddy simulations (LES) of a vertical turbulent channel flow laden with a very large number of solid particles are performed. The motivation for this research is to get insight into fundamental aspects of co-current turbulent gas-particle flows, as encountered in riser reactors. The particle volume fraction equals about 1.3%, which is relatively high in the context of modern LES of two-phase flows. The channel flow simulations are based on large-eddy approximations of the compressible Navier-Stokes equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 72 publications
3
46
0
Order By: Relevance
“…This effect has been found before in DNS and LES (large-eddy simulation) of wall-bounded particle-laden flow at high mass loading. 7,26 In case 2Wn, the number of particles is smaller than in cases 2 W and 2Wcp. This results in a smaller reduction of the fluctuating wall-normal velocity r.m.s.…”
Section: A Velocity and Particle Concentrationmentioning
confidence: 86%
See 2 more Smart Citations
“…This effect has been found before in DNS and LES (large-eddy simulation) of wall-bounded particle-laden flow at high mass loading. 7,26 In case 2Wn, the number of particles is smaller than in cases 2 W and 2Wcp. This results in a smaller reduction of the fluctuating wall-normal velocity r.m.s.…”
Section: A Velocity and Particle Concentrationmentioning
confidence: 86%
“…This results in a smaller reduction of the fluctuating wall-normal velocity r.m.s. Hence, the turbophoresis is between that of case 2 W and 1 W. It is known that four-way coupling plays a role if the particle volume fraction is large, see for example Vreman et al, 7 where the particle volume fraction is larger than 1%. Turbophoresis leads to increased particle volume fractions close to the walls, but this effect is significantly reduced by the two-way coupling, so that also close to the walls, the particle volume fraction stays well below 1%, motivating our use of two-way coupling as the dominant mechanism throughout the domain.…”
Section: A Velocity and Particle Concentrationmentioning
confidence: 93%
See 1 more Smart Citation
“…Others have shown that p-p collisions significantly flatten the mean particle velocity profile and the mean particle volume fraction velocity profile at low volume fractions (Li et al 2001;Yamamoto et al 2001;Vreman 2007;Nasr et al 2009). At larger volume fractions p-p collisions were shown to enhance the transfer from the kinetic energy in the streamwise particle velocity fluctuations to the kinetic energy in both the normal and spanwise particle velocity fluctuations (Vreman et al 2009). …”
Section: −1mentioning
confidence: 99%
“…For this purpose the point-particle approximation is very suitable, allowing to evaluate the trajectories of individual particles at low computational cost [44,58]. For resolving the gas flow we use a symmetry-preserving finite-volume discretization on a staggered grid [56].…”
Section: Introductionmentioning
confidence: 99%